Seasonal variability of oxidative stress markers in city bus drivers. Part I. Oxidative damage to DNA - Rossner, Pavel; Svecova, Vlasta; Milcova, Alena; Lnenickova, Zdena; Solansky, Ivo; Sram, Radim J (Mutation research, 2008)
We investigated the seasonal variability of 8-oxodeoxyguanosine (8-oxodG), a marker of oxidative damage to DNA, in urine of 50 bus drivers and 50 controls in Prague, Czech Republic, in three seasons with different levels of air pollution: winter 2005, summer 2006 and winter 2006. The exposure to environmental pollutants (carcinogenic polycyclic aromatic hydrocarbons, c-PAHs, particulate matter (PM), and volatile organic compounds (VOC)) was monitored by personal and/or stationary monitors. For the analysis of 8-oxodG levels, the ELISA technique was used. Bus drivers were exposed to significantly higher levels of c-PAHs in winter 2006, while in the other two seasons the exposure of controls was unexpectedly higher than that of bus drivers. We did not see any difference in VOC exposure between both groups in summer 2006 and in winter 2006; VOC were not monitored in winter 2005. 8-OxodG levels were higher in bus drivers than in controls in all seasons. The median levels of 8-oxodG (nmol/mmol creatinine) in bus drivers vs. controls were as follows: winter 2005: 7.79 vs. 6.12 (p=0.01); summer 2006: 6.91 vs. 5.11 (p<0.01); winter 2006: 5.73 vs. 3.94 (p<0.001). Multivariate logistic regression analysis identified PM2.5 and PM10 levels, measured by stationary monitors during a 3-day period before urine collection, as the only factors significantly affecting 8-oxodG levels, while the levels of c-PAHs had no significant influence.
Keywords: Biomarkers; roční období; lidé; Occupational Exposure; polycyklické aromatické uhlovodíky; látky znečišťující vzduch v pracovním prostředí; Deoxyguanosine; Seasons; 8-Hydroxy-2'-Deoxyguanosine; oxidační stres; Air Pollutants, Occupational; Environmental Pollutants; 8-hydroxy-2'-deoxyguanosin; Humans; Carcinogens, Environmental; biologické markery; Particulate Matter; Motor Vehicles; Oxidative Stress; karcinogeny životního prostředí; DNA Damage; Environmental Monitoring; pevné částice; Polycyclic Aromatic Hydrocarbons; deoxyguanosin; monitorování životního prostředí; motorová vozidla; pracovní expozice; poškození DNA; látky znečišťující životní prostředí